Game-based English speaking instruction for young learners - Lin, Chan-Li; Tien, Fu-I (Journal of Education and Learning (EduLearn), 2026)
This study explored the implementation of a teacher-designed board game, “Castle of Dread”, to enhance the English oral proficiency of sixth-grade elementary school students in Taiwan. Grounded in action research methodology, the study was conducted over nine weeks with 26 students, incorporating three thematic instructional cycles: clothing, leisure activities, and illnesses. The research aimed to examine students’ speaking performance before and after gamified instruction, their motivational changes, and the challenges encountered by the teacher. Data sources included classroom observations, oral speaking assessments, student interviews, and reflective journals. Results showed that students demonstrated improved fluency and confidence in speaking, particularly among low-achieving learners. In addition, the game-based activities fostered higher motivation and peer collaboration. The teacher’s reflective practice led to instructional adaptations such as scaffolding strategies and rule simplification. This study contributes to the growing literature on game-based learning (GBL) in English as a foreign language (EFL) context and offers practical implications for integrating educational games in elementary language classrooms.